Interactions between the nematodes Ditylenchus angustus and Aphelenchoides besseyi on rice: population dynamics and grain yield reductions - Latif, Mohammad Abdul; Haque, Ahsanul; Tajul, Mohammad Islam; Monsur, Mohammad Abul; Yusop, Mohd Rafii (Firenze University Press, 2013)
Experiments were conducted in pots and an irrigated rice (Oryza sativa) field to determine the impact of mixed or single nematode inoculations with Aphelenchoides besseyi and Ditylenchus angustus on nematode population dynamics and yield attributes of rice cv. BR3. The reproduction rates were greater in a single nematode species inoculated with either A. besseyi or D. angustus compared to their mixed inoculation. This was probably due to competition between the two nematode species. Greater incidences of white-tip and ufra diseases were observed with single nematode species inoculations compared to mixed species inoculations. Total yield losses ranged from 24 to 47% from mixed inoculations (different ratios) of D. angustus and A. besseyi, compared to 62% from inoculation with D. angustus and 16% from A. besseyi. Single species inoculations (with either D. angustus or A. besseyi) gave greater disease incidence and greater yield reductions than mixed inoculations with both nematodes.